Regulation of RIPK1 activation by TAK1-mediated phosphorylation dictates apoptosis and necroptosis - Jiefei Geng; Yasushi Ito; Linyu Shi; Palak Amin; Jiachen Chu; Amanda Tomie Ouchida; Adnan Kasim Mookhtiar; Heng Zhao; Daichao Xu; Bing Shan; Ayaz Najafov; Guangping Gao; et al. (Nature Communications, 2017)
TNFα can promote three distinct mechanisms of cell death: necroptosis, RIPK1-independent and dependent apoptosis. Here the authors show that TNFα-induced phosphorylation of RIPK1 in the intermediate domain by TAK1 plays a key role in regulating this decision.